Effect of ceramic reinforcement on the microstructural, mechanical and tribological behavior of Al-Cu alloy metal matrix composite - Aktar Zahid Sohag M.; Gupta P.; Kondal N.; Kumar D.; Singh N.; Jamwal A. (My University, 2025)
Aluminum metal matrix composites are highly demanding materials at present time because of their excellent thermal, mechanical and electrical properties which makes them promising choice in material selection for many engineering applications. In the present study aluminum-copper alloy matrix composite reinforced with SiC and TiC is fabricated by stir casting process. In this study amount of copper is fixed as 2 wt% and SiC-TiC content is varied from (2 wt% to 8 wt%) at an interval of 2 wt%. XRD analysis revealed that there is no reaction between matrix and reinforcement phase. Microstructural analysis shows that there is uniform distribution of reinforcement particles. Density and hardness of composites were investigated which shows that increase in reinforcement content increases the hardness while there is decrease in density. Wear study reveals that composites reinforced with SiC and TiC exhibit lower wear rates. It is expected that this composite is beneficial for shipping applications. © 2019 Elsevier Ltd. All rights resrved.